Expresión autoetnográfica: consciencia de oposición en las literaturas de los Estados Unidos - Valdez, Charli G. (Revista de Antropología Social, 2008)
A study of autoethnography and its polemic offers an especially salient mode of reading a particular type, or pattern, of oppositional racial consciousness in American Literature, then. This article will consider criticism of autoethnography -such as regards its “narcissistic” and purportedly essentialist tendencies- and rapidly review a number of scholars attempting to define and shape the field of autoethnography A rapid-fire consideration of multiple definitions of a term in a contested field such as autoethnography is really the only way to responsibly mobilize the notion in a literary critique and also avoids the mistake some make in too hastily appropriating a definition that will make it easy to give their work an unusual angle of attack. Given the frequently insufficiently researched use of the term, this article will ultimately argue for a delimiting definition of the “genre” which takes into account Chela Sandoval’s theory of oppositional consciousness and Pratt’s particular definition of autoethnography itself. In so doing, it will present two specific examples from 20th Century American Literatures that give voice to a peculiar mode of autoethnographic expression.
Keywords: Autoethnography; Zora Neale Hurston; Rosario Ferré; Latino Literature; Oppositional consciousness